1996
DOI: 10.1002/etc.5620150326
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics‐based survival analysis in bioassays using nonpersistent chemicals

Abstract: Present statistical analysis of survivorship data obtained from bioassays using nonpersistent toxicants does not explicitly take into account that exposure decreases with time due to degradation of the toxicant. Such a situation typically occurs in static aquatic toxicity tests and in soil tests. We develop a model for the analysis of survival data obtained in such experiments and show how estimates for the initial LC50, the degradation rate constant, and the elimination rate constant may be obtained from obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 17 publications
1
62
0
Order By: Relevance
“…The same model formulation was applied by Widianarko and Van Straalen [19], although in their case, the factor k dis did not reflect a change in bioavailability but a change in total concentration of a pesticide in soil.…”
Section: Soil and Earthworm Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same model formulation was applied by Widianarko and Van Straalen [19], although in their case, the factor k dis did not reflect a change in bioavailability but a change in total concentration of a pesticide in soil.…”
Section: Soil and Earthworm Data Analysesmentioning
confidence: 99%
“…Chem. 19,2000 T. Jager et al able, given the lag phase observed in the degradation), an additional estimate for k 2 is obtained. Especially for PHE, this results in a higher value than found in the depuration phase (Table 2), which compares better to the literature data and reveals a relationship between k 2 and K ow (Fig.…”
Section: Elimination From Earthwormsmentioning
confidence: 99%
“…However, in the present study, no decrease in lipid levels in earthworms was observed. Induced metabolism may also result in peak accumulation curves [29,31]. However, earthworm cytochrome P450 monooxygenase enzyme activities are considerably lower than those found in many other organisms [32], with only 1% or less of pyrene metabolized by E. andrei in one study [20], so metabolism is not thought to be an important elimination route for aromatics such as PAHs in earthworms [20,22].…”
Section: Accumulation and Elimination Of F2 F3a And F3bmentioning
confidence: 98%
“…Conventional toxicological approaches and concepts based on the premise of constant exposure to chemicals may no longer be adequate to deal with time-variable exposure. Analysis of variable exposures appears to be an area of increasing attention, both in experimental [2][3][4][5] and modeling studies [1,[6][7][8][9][10][11]. Most of the proposed models that deal with timevariable exposure are based on the concept of critical body residues (i.e., the internal concentration above which toxicity manifests) [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Objectives of the present study were to determine the toxicokinetics of zinc in P. reticulata, to analyze the effect of time-varying exposure on the survival of guppies, and to evaluate the applicability of a toxicokinetics-based survival model [11] to the present data.…”
Section: Introductionmentioning
confidence: 99%